2002
DOI: 10.1080/0260293022000009285
|View full text |Cite
|
Sign up to set email alerts
|

Student Perspectives on Teaching and its Evaluation

Abstract: The research on student ratings of instruction, while voluminous, has had minimal focus on the perceptions of the students who do the ratings. The current study explored student perspectives on course and teacher ratings as well as some issues related to teaching effectiveness and faculty roles. It was found that students are generally willing to do evaluations and to provide feedback, and have no particular fear of repercussions. However, they have little con dence that faculty or administrators pay attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
2
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 34 publications
3
62
2
3
Order By: Relevance
“…For this reason, it is advantageous if teachers signal to students changes they have made in their teaching as a consequence of student feedback (Spencer & Schmelkin, 2002). The students spoke in an approbatory manner of teachers who consulted with them on action plans they had formulated in response to formal feedback.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is advantageous if teachers signal to students changes they have made in their teaching as a consequence of student feedback (Spencer & Schmelkin, 2002). The students spoke in an approbatory manner of teachers who consulted with them on action plans they had formulated in response to formal feedback.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fraser (1998), Shuell (1996, and Shulman (1986), it can be assumed that students' learning and motivation are determined by their perceptions, and not by teachers' intentions and emotions (Mayer, Solovey & Caruso, 2000). Spencer and Schmelkin (2002) found that the instructor's personal characteristics were perceived by students as preferred effective teaching attributes. These preferred personal characteristics included (a) demonstrating concern for students, (b) valuing learners' opinions, (c) clarity in communication, and (d) openness toward varied opinions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Due to the fact that SET might affect the employment decisions, instructors might grade leniently. Spencer and Schmelkin (2002) argued that if schools use only one evaluation conducted at the end of the semester, there might be a tendency that students remember more about what the instructor has done right before the evaluation. Although, at the end of semester, students could give an overall evaluation, students' attitudes towards the evaluations are seldom inquired.…”
Section: The Current Situation Of Setmentioning
confidence: 99%